A Tectonic Manifesto - Robert Stern; Taras Gerya; Paul Tackley (Perspectives of Earth and Space Scientists)
Abstract Tectonics is the scientific discipline that studies the relationship between planetary convection and surface deformation and magmatism. In recent years global tectonic regimes and planetary evolution have become foci of astronomical and planetological research dealing in particular with potential habitability of planets orbiting other stars in our galaxy (exoplanets). This broadens the scientific impact of “tectonics” and makes it useful to outline a few guiding principles. For many, the term “tectonics” is synonymous with Plate Tectonics on Earth, but it should not be limited to only the planet we know best. Specifically, the concept should be generalized to encompass other rocky planets and moons in our Solar System and exoplanets. This article summarizes 15 general concepts about how such bodies are expected to behave.